(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
This study aims to analyze the potential application of sharf accounting for foreign currency exchange transactions conducted by PT. Markaz Sharraf Pamekasan as an entity that organizes non-bank foreign exchange business activities by using qualitative research. The results of the study show that the application of sharf accounting for foreign exchange transactions has the potential to be carried out, because it is supported by the availability of sufficient regulations, both from Bank Indonesia as a regulator, DSN-MUI as a fatwa institution, and IAI which issues accounting standards. In addition, the dynamics of foreign exchange transactions have met the exchange criteria required by the three institutions. The challenge that still exists is the availability of competent resources in applying these sharf accounting standards, because changing the standards will also change the financial statements that must be presented.